Case vignettes-based workshops as a tool to facilitate interdisciplinary engagement with complex problems in sustainability education - Martin Mickelsson; Emma Oljans (Discover Sustainability)
Abstract Antimicrobial resistance (AMR) is an emerging challenge for sustainability education. This study examines how case vignettes as a tool, when integrated within participatory workshops, foster interdisciplinary collaboration and participatory research, focusing on their application to the complex challenge of AMR. Two one-day participatory research workshops were conducted at higher educational institutions, involving a total of 60 interdisciplinary participants, including 10 educators and 20 students from two universities in Zimbabwe. A thematic analysis using analytical categories based on previous literature resulted in the development of six themes, ranging from developing systems thinking, and thorough decision justification, to co-created knowledge. These themes highlight the potential of case vignette-based workshops to support collaborative problem-solving and knowledge exchange in addressing complex societal challenges like AMR. Such as interdisciplinary engagements, effectively highlighting the complex and “wicked” character of AMR that spans domains of knowledge, ethics, policy, and practical intervention to which each discipline can contribute through the use of integrated case vignettes.